Magnetocrystalline and magnetoelastic constants determined by magnetization dynamics under static strain. (10th September 2018) - Duquesne, J-Y; Hepburn, C; Rovillain, P; Marangolo, M
Abstract: We consider here the magnetization dynamics induced in a ferromagnet by magnetoelastic coupling, after application of a step like strain. We derive the time evolution of the magnetization vector. We show that the material micromagnetic parameters (and specifically magnetic anisotropy and magnetoelastic coupling) can be derived from measurable quantities, i.e. the precession frequency, relaxation time and phase lag between the precession angles. Such measurements can be performed by state of the art time resolved Kerr experiments.